RURAL LOGISTIK: STRATEGI PENINGKATAN KEUNTUNGAN PETANI STROBERI DI DESA SUKARESMI, RANCABALI, CIWIDEY - Irfan Rayyana Ardiansyah; Della Apriani; Septian Glenn Alexander Godjang; Riskita Farida Sihaloho (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
The Strawberry farmers in Sukaresmi Village, Rancabali, Bandung still face challenges with in crop distribution, resulting in suboptimal profits. Their reliance on wholesalers and middlemen as distribution intermediaries limits the profits farmers can earn. This study aims to analyze the potential for increasing farmers’ profits through the production of ‘The Love’ strawberries and by shifting the role of middlemen from distributors to suppliers. Data were collected through field observations and interviews with farmers, then analyzed using dynamic systems approach with the aid of AnyLogic. Simulations were conducted over 90 days under existing conditions, the ‘The Love’ variety scenario, and the middleman scenario. Simulation results show that the existing conditions yield a profit of IDR28.336.345,65. ‘The Love’ strawberry scenario increases profits to IDR60.022.724,10. Meanwhile, the scenario where collectors act as suppliers yields the highest profit of IDR154.068.052,17, with total sales reaching 8,009 kilograms during the simulation period. The research results indicate that involving collectors as suppliers is the most optimal alternative for increasing the profits of strawberry farmers in Sukaresmi